Cho hàm số $y = \frac{{\cos 2x}}{{1 – \sin x}}$ . Tính đạo hàm $y’\left( {\frac{\pi }{6}} \right)$ bằng

Cho hàm số $y = \frac{{\cos 2x}}{{1 – \sin x}}$ . Tính đạo hàm $y’\left( {\frac{\pi }{6}} \right)$ bằng
A. $y’\left( {\frac{\pi }{6}} \right) = 1$ .

B. $y’\left( {\frac{\pi }{6}} \right) = – 1$ .

C. $y’\left( {\frac{\pi }{6}} \right) = \sqrt 3 $ .

D. $y’\left( {\frac{\pi }{6}} \right) = – \sqrt 3 $ .

Hướng dẫn giải

Chọn D.

Vận dụng công thức tính đạo hàm sin cos đã được học:

$\begin{array}{l}
y’ = \frac{{\left( {\cos 2x} \right)’.\left( {1 – \sin x} \right) – \cos 2x\left( {1 – \sin x} \right)’}}{{{{\left( {1 – \sin x} \right)}^2}}}\\
= \frac{{ – 2\sin 2x\left( {1 – \sin x} \right) + \cos 2x.cosx}}{{{{\left( {1 – \sin x} \right)}^2}}}
\end{array}$ .
$\begin{array}{l}
y’\left( {\frac{\pi }{6}} \right) = \frac{{ – 2.\frac{{\sqrt 3 }}{2}\left( {1 – \frac{1}{2}} \right) + \frac{1}{2}.\frac{{\sqrt 3 }}{2}}}{{{{\left( {1 – \frac{1}{2}} \right)}^2}}} = \frac{{ – \frac{{\sqrt 3 }}{2} + \frac{{\sqrt 3 }}{4}}}{{\frac{1}{4}}}\\
= 4\left( { – \frac{{\sqrt 3 }}{2} + \frac{{\sqrt 3 }}{4}} \right)\\
= – 2\sqrt 3 + \sqrt 3 = – \sqrt 3
\end{array}$ .